2013
DOI: 10.19070/2328-353x-130001
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese may develop type 2 diabetes with smaller increases in body mass index and waist circumference than Taiwanese

Abstract: Background: Obesity is associated with development of diabetes. However, it seems that the level of obesity in association with diabetes may differ from country to country. Aim:To compare BMI and waist circumference in diabetic patients between Vietnamese and Taiwanese.Methods: Subjects were found to be diabetes mellitus by the health examination and had not treatment before. They were 163 Vietnamese and 298 Taiwanese. Body weight, height and waist circumference were measured Results: Compared with Taiwanese, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In line with a report in Japan [18], the present study showed the association of SUA with IFG and T2D in Vietnamese population with the BMI mean <25 (21.9 ± 2.7) kg/m 2 , whereas the other reported that the association between SUA and incident prediabetes was not significant among Caucasian population with BMI <25 kg/m 2 [26]. This indicates the important difference in BMI between Vietnamese and Caucasians in the pathogenesis of type 2 diabetes [27], and Vietnamese may develop type 2 diabetes with smaller increases in BMI than Taiwanese [28].…”
Section: Discussionmentioning
confidence: 99%
“…In line with a report in Japan [18], the present study showed the association of SUA with IFG and T2D in Vietnamese population with the BMI mean <25 (21.9 ± 2.7) kg/m 2 , whereas the other reported that the association between SUA and incident prediabetes was not significant among Caucasian population with BMI <25 kg/m 2 [26]. This indicates the important difference in BMI between Vietnamese and Caucasians in the pathogenesis of type 2 diabetes [27], and Vietnamese may develop type 2 diabetes with smaller increases in BMI than Taiwanese [28].…”
Section: Discussionmentioning
confidence: 99%